Reliability and validity of the six-minute step test in assessing the functional capacity of hemodialysis patients - Carla Cristina Lima; Maria Eduarda Godoy; Débora Kellen Ferreira Fratoni; Elaine Paulin (PeerJ, 2025)
Purpose Hemodialysis patients often experience functional limitations that are challenging to assess due to equipment and space constraints. The 6-min step test (6MST) requires little space and a small standardized ergometer, making it more accessible and feasible in various healthcare settings, when compared to the cardiopulmonary exercise test (CPET) and the 6-min walk test (6MWT). Thus, the aim of this study is to evaluate the test-retest reliability and concurrent validity of the 6MST for assessing the functional capacity of hemodialysis patients. Methods Assessments conducted included anthropometry, spirometry, 6MWT, and 6MST. These two tests were randomized and performed on alternate days. Two 6MSTs and two 6MWTs were conducted with a minimum interval of 30 min between them. Results The study involved 32 participants, 67% men (n = 22) and 33% women (n = 10), with an average age of 57 ± 13 years and body mass index (BMI) of 28.6 ± 5.2 kg/m2. The 6MST demonstrated high test-retest reliability (ICC = 0.94 (95% CI [0.85–0.97]; p < 0.001)) and a strong correlation between the number of steps performed in the 6MST and the distance covered in the 6MWT (r = 0.87; p < 0.001). A learning effect was observed, with a 7% improvement on retesting. Conclusion The 6MST provides a feasible, reliable assessment option for hemodialysis patients and could be easily implemented in clinics lacking space and specialized equipment. Limitation of the present study are being a single-center investigation with a small sample size, thus limiting generalizability, and the variability of patient conditions, which may have influenced the results. Future research should explore the 6’ long-term stability, responsiveness, and impact on patient-centered outcomes, as well as its applicability across different hemodialysis populations and clinical settings, to improve its clinical usefulness.